Analysis of mounting induced strain in semiconductor structures by means of spatially resolved optical modulation techniques - Pierściński, Kamil; Piwoński, Tomasz; Ochalski, Tomasz J.; Kowalczyk, Emil; Wawer, Dorota; Bugajski, Maciej (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
A wide range of applications of high-power diode lasers is connected with the tendency towards device miniaturization resulting in increased power densities. To manage the thermal load, the chips or arrays of chips (the so-called laser lines or cm–bars) have to be mounted with low thermal resistance on a heat sink of high thermal conductivity. These measures potentially introduce mechanical strain and defects into the semiconductor chips affecting the parameters of laser emission, e.g., spectral position. The ability of optical modulation techniques to monitor spatial strain distribution along the devices was evaluated.
Optica Applicata, Vol. 35, 2005, nr 3, s. 605-610
Keywords: optyka; electroreflectance; mounting induced strain; laser bar